Kewajiban Administrasi Perpajakan Wajib Pajak dalam Sistem Self Assessment - FC Susila Adiyanta (Administrative Law and Governance Journal, 2022)
Abstract: The purpose of this study is to identify and explain the taxpayer's tax obligations and self-assessment systems in national tax practice. This study uses a doctrinal legal approach.From the research results, it can be concluded: a) in the self-assessment system, taxpayers are required to register themselves; b) perform payment calculations; c) pay taxes owed; and d) report its obligations by filling out an SPT. The recommendations of this research are: a) understanding and awareness of taxpayers/taxpayers on their rights and obligations is a determining factor in complying with tax laws and regulations; b) empowerment of taxpayers to increase knowledge and understanding of taxpayers on tax rights and obligations which are expected to obtain taxpayer compliance (voluntary tax compliance); and c) orderly administration in tax services is the first step in improving efficient and effective administrative services, as well as realizing the application of justice in the treatment of taxpayers. Keywords: Tax administration obligations, taxpayers Abstrak: Tujuan dari penelitian ini adalah untuk mengetahui dan menjelaskan tentang kewajiban administrasi perpajakan wajib pajak dan penggunaan sistem self assessment dalam praksis perpajakan nasional.  Penelitian ini menggunakan pendekatan hukum doktrinal. Dari hasil penelitian diperoleh kesimpulan: a) di dalam sistem self assessment, wajib pajak mempunyai kewajiban untuk mendaftarkan diri; b) melakukan sendiri penghitungan pembayaran;  c) membayar pajak terutang; dan d) melaporkan kewajiban pajaknya dengan mengisi SPT. Rekomendasi penelitian ini adalah : a) Pemahaman dan kesadaran wajib pajak/ penanggung pajak atas hak-hak dan kewajibannya merupakan faktor penentu dalam mematuhi ketentuan perundang-undangan perpajakan; b) p emberdayaan wajib pajak dimaksudkan untuk meningkatkan pengetahuan dan pemahaman wajib pajak atas hak dan kewajiban perpajakannya yang diharapkan akan dapat membentuk kepatuhan sukarela wajib pajak (voluntary tax compliance); dan c) Tertib administrasi dalam pelayanan perpajakan merupakan langkah awal dalam meningkatkan  pengelolaan pelayanan administrasi perpajakan yang efisien dan efektif, serta mewujudkan aspek keadilan dalam perlakuan pengenaan wajib pajak. Kata kunci: Kewajiban administrasi pajak, wajib pajak